Epimedium protects against dyszoospermia in mice with Pex3 knockout by exerting antioxidant effects and regulating the expression level of P16 - Zhao, Haiyang; Zhao, Tingting; Yang, Jihong; Huang, Qianqian; Wu, Hua; Pan, Yueyun; Wang, Hui; Qian, Yun (Cell death & disease, 2022)
Oxidative stress (OS) is one of the primary factors leading to male infertility. Oral administration of antioxidants has thus far been found to significantly improve the quality of human sperm. Therefore, antioxidant treatment has become the consensus among international experts on male infertility. In this study, peroxisomal biogenesis factor 3 ( Pex3 )-knockout (KO, −/−) mice were used as a model to compare the efficacy of three types of traditional Chinese medicine (TCM) granules (Epimedium [YYH], Cuscuta [TSZ], and Rhodiola [HJT]) for male reproductive function rescue. YYH was revealed to be the best and exerted a rescue effect on Pex3 −/− mice with spermatogenesis defects. In addition, YYH prominently reduced ROS levels in the testes, inhibited DNA oxidative damage in spermatogenic cells, promoted the proliferation of spermatogenic cells, and inhibited apoptosis in Pex3 −/− male mice. Furthermore, the mechanism by which YYH ameliorated dyszoospermia was confirmed via the establishment of cyclin-dependent kinase inhibitor 2 A (P16Ink4a)-KO mice. Specifically, Pex3 −/− mice produced elevated amounts of ROS, which damaged germ cell DNA and further activated the signaling pathway of the cell senescence regulatory protein P16-CDK6, resulting in cell cycle arrest and eventually contributing to spermatogenesis dysfunction. YYH supplementation partially corrected the associated phenotype in gene KO mice by affecting P16 expression levels, thus improving the reproductive outcome to a certain extent.